Linea lombarda tra ieri e oggi: la delicatezza di un problema letterario (Configurazioni. Ricerche sulla poesia contemporanea, 2023)
The article is an extract of my Ph.D. Thesis (Da Linea lombarda a via a galassia: una «cosa delicata» e ricca. Ripensare la complessità da un fenomeno di poesia), on Anti-Canon in the late Twentieth Century. It focuses on the historical and literary example that was the main issue of the Thesis and it can be indexable as follows (six paragraphs): 1. Antinomy of the assumptions (1952); 2. Content of the editorial project; 3. Diverse sense of engagement (especially, Erba’s and Sereni’s); 4. Critical reception (from the Fifties to the Noughties); 5. Method of the Curatorship (first book and its reedition by Luzzi -1989-); 6. Unpublished and recent implications (conclusions).
Keywords: Poesia Italiana del Novecento; Linea lombarda; Luciano Anceschi; Fenomenologia; canone letterario